Study on the Influence of the Preload Coefficient on the Tilting Pad Bearing of High Speed Gear Transimission - Yang Linjie; Cao Zhigang; Wang Jingyuan; Liu Chunbo; Wang Zhimin (Jixie chuandong)
Tilting pad bearings are widely used in modern industry because of their inherent stability，and related research has flourished. However，the study on the tilting pad bearing preload coefficient mainly focuses on the field of low rotational speed. The DyRoBeS software is used as the research tool，and the commonly used five tilting pad bearing is taken as the research object. The influence of the preload coefficient on the working performance of the tilting pad bearing under the high rotational speed conditions of 20 000 r/min，40 000 r/min and 60 000 r/min. The analysis results will provide theoretical basis for the design and application of the tilting pad in high-speed gear transmission. In the process of preload coefficient increased from 0.1 to 0.7，there is no effect on the power loss，but the maximum oil film pressure and stiffness coefficients are increased，the minimum oil film thickness and damping coefficients are decreased. The mixed setting of the preload coefficients affected the pressure distribution of each tilting pad，the bearing performance parameters except the minimum oil film thickness is obviously increased. The conclusion will play a positive role in the optimization design of tilting pad bearing with high rotation rate.